Psychological Study Of Teachers` Perception Of Creativity Importance - Gevorgyan, Astghik (Զանգակ հրատ.)
The purpose of the article is to study the perception of creativity of teachers and experts in the field of education and to present the importance of creativity among the professional psychological qualities of a teacher. To achieve this goal, we conducted a theoretical analysis of creativity and teachers' creativity and did a questionnaire study of experts in the field of education and teachers. Based on the research data we concluded that experts and teachers value creativity more than its components: curiosity, versatility, originality of thinking and ingenuity. This proves that there is no clear understanding of creativity among teachers and experts. They highlight creativity. However, they have no perception of the exact content of it ․ It turned out also that the importance of creativity and its components as professional qualities for teachers rises along with teachers' work experienc
Keywords: Psychology